Rethinking Implicit Leadership Theories: Tomorrow's Leaders are Collective, Generative, and Adaptive. Issue 3 (23rd November 2020) - Wilson, Josh; North, Malcolm; Morris, Duston; McClellan, Rhonda
Abstract : Despite the importance of implicit leadership theories (ILTs) and the prevalence of egalitarian leadership models, few studies address the lack of collective leadership constructs in ILTs. Given the dominance of leadership instruments using leader‐centric measurements, a popular ILT questionnaire was augmented with 16 new items that represented collective, emerging, and egalitarian constructs. A principal components analysis was conducted on a 37‐item questionnaire with 528 university faculty, staff, and students. The five‐component solution explained 52.5% of the total variance. The model retained two previous ILT components (dedication and intellectual) and found three new ones. These were identified as collective, generative, and integrative and consisted of 12 items that represent collective ILTs. The findings suggest that prototypical and leader‐centric ILTs are giving way to collective models.